Solidaritas Mekanik Paguyuban Persatuan Keluarga Kayu Aro Kerinci (PK3P) di Kota Padang - Wibi Wijaya; Tuti Lestari; Arifah Wahyuni (Bakaba, 2018)
Solidarity shows a state of relationship between individuals or groups based on moral feelings and shared beliefs reinforced by shared emotional experiences. As for the Padang Aro Kerinci Family Family Association in Padang City, it contains migrants or migrants from outside Padang. The people who are members of this community are dominated by the Javanese people of the Kayu Aro District of Kerinci, Jambi. The PK3P Circle of Friends has been established since 1995 or is already 24 years old. This research is a qualitative research. Determination of informants is done by Purposive Sampling. Based on this research, it can be concluded that, the form of mechanical solidarity of the aro kerinci family family unity in Padang city based on the feeling elements in the community, among other elements of affection namely feeling arises due to someone trying to identify themselves with as many people in the group so that all of them can call themselves "our group", "our feelings" and so on. Furthermore, the continuity and mutual need of individuals who are members of the community feel themselves dependent on their community or community which includes physical needs or psychological needs. The group that is incorporated in the community meets the physical needs of someone, for example for food and shelter.